Memorie - Oulman Bensaude, Jane (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2016)
Jeanne (Jane) Oulman Bensaude belonged to a Parisian Jewish upper middle class family related to the world of finance and fully involved in the cultural and political life of Paris in the second half of the nineteenth century. In Memorie Jane recalls the family environment, travels, readings, living rooms, meetings with poets and writers, musicians and politicians. She narrates her passion for music and writing, to which she dedicated herself in Lisbon, where she lived after the marriage to Alfredo Bensaude. The story of a development, of a life divided between France and Portugal, Jane's autobiography offers many reasons of interest: from within the Oulman family life, in the education of sons and daughters, in observance of the rites, in the interweaving of family affairs with the history of France, it represents a rare document of the process of assimilation of French Judaism to the values of the nation.